The biological functions of Lonicera japonica in animal husbandry and its application in green breeding - Zhang, Xia; Huo, Hailong; Hu, Lijuan; Yang, Fuhua; Deng, Yunze; Hu, Xiaojing; Wang, Haizhen; Huo, Jinlong (Frontiers in Veterinary Science, 2026)
Lonicera japonica (honeysuckle) is a traditional Chinese medicinal herb known for its properties of clearing heat, detoxifying, cooling blood, dispersing wind, and exerting anti-inflammatory and antibacterial effects. Research conducted on domestic animals, the bioactive constituents found in Lonicera japonica have been demonstrated to potentiate the immune response, thereby augmenting the animal’s disease resistance capabilities. The antioxidant ingredients effectively diminish free radicals within the animal, thereby slowing down cellular aging and enhancing the quality of animal-derived products. The antibacterial and anti-inflammatory properties of its constituents can effectively harmonize the animal’s intestinal microbiota and refine the gastrointestinal milieu. This equilibrium aids in bolstering nutrient uptake and refining the efficiency of feed utilization. Its antiviral components can minimize the presence of drug residues in animal-derived products, thereby enhancing product safety and bolstering market competitiveness. The attributes highlighted demonstrate that the application of Lonicera japonica aligns with the principles of green, eco-friendly, and sustainable development. Its usage promotes the advancement of ecological agriculture and the circular economy, fostering a more harmonious and sustainable approach to farming. This paper primarily reviews the key active constituents, therapeutic potential, biological functions of Lonicera japonica, and its contemporary applications in livestock and poultry farming. The objective is to offer a comprehensive reference for optimizing the production efficiency and enhancing the product quality of livestock and poultry, as well as for substituting antibiotics with Lonicera japonica in animal husbandry.